Sinonasal Melanoma: A Single Institutional Analysis and Future Directions - Manton, Taylor; Tillman, Brittny; McHugh, Jonathan; Bellile, Emily; McLean, Scott; McKean, Erin (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Sinonasal melanoma is a rare disease with a high mortality rate. The surgical management paradigm has significantly changed over the past decade with the introduction of expanded endonasal techniques. There have also been advances in management of metastatic and locally advanced disease with the advent of immunotherapy.Methods Single-institution retrospective review of adult patients with sinonasal melanoma, surgically managed at the University of Michigan over a 9-year period. Thirty-one patients met inclusion criteria. All patients were retrospectively staged according to the 7th Edition AJCC staging system for mucosal melanoma. Parameters that may affect survival were analyzed using Cox's proportional hazard models and survival outcomes were analyzed with the Kaplan–Meier method. Additionally, a review of three patients with distant metastatic disease receiving immunotherapy is presented.Results Most patients were managed endoscopically (67%), and had stage III disease (71%). However, 57% of stage IVB tumors were successfully managed endoscopically. Stage statistically impacted overall survival whereas distant control was impacted by stage, site of origin, mitotic rate, and necrosis. The 2-year overall survival for all stages was 77% which declined with advanced disease. Two-year locoregional control and distant control showed similar trends.Conclusion Treatment of sinonasal melanoma has drastically changed over the past decade with increased use of expanded endonasal techniques. Our review revealed excellent 2-year overall survival in stage III disease with an appreciable decline in survival in more advanced disease. Immunotherapy may play a large role is future management given the high-risk of distant metastasis.
Keywords: sinonasal malignancy; mucosal melanoma; outcomes; immunotherapy; expanded endonasal technique